Topographical measurement of the attachments of the central band of the interosseous membrane on interosseous crests of the radius and ulna - Suk-Hwan Jang; Kyung-Whan Kim; Hyo Seok Jang; Yeong-Seok Kim; Hojin Kim; Youngbok Kim (Clinics in Shoulder and Elbow, 2021)
Background To suggest a reasonable isometric point based on the anatomical consistency of interosseous membrane (IOM) attachment in association with topographic characteristics of the interosseous crests, the footprints of the central band (CB) of the IOM on the radial and ulnar interosseous crests (RIC and UIC) were measured. Methods We measured the distance from the CB footprints from each apex of both interosseous crests in 14 cadavers and the angles between the forearm axis of rotation (AOR) and the distal slopes of the RIC and UIC in 33 volunteers. Results The CB footprints lay on the downslope of both interosseous crests with its upper margin on average 3-mm proximal from the RIC's apex consistently in the radial length, showing normality (p>0.05), and on average 16-mm distal from the UIC's apex on the ulna without satisfying normality (p<0.05). The average angle between the UIC's distal slope and the AOR was 1.3°, and the RIC's distal slope to the AOR was 14.0°, satisfying the normality tests (p>0.05), and there was no side-to-side difference in both forearms (p<0.05). Conclusions The CB attached to the downslope just distal to the RIC's apex constrains the radius to the UIC that coincides with the AOR of the forearm circumduction, maintaining itself both isometrically and isotonically.